Chondroitin synthase‐3 regulates nucleus pulposus degeneration through actin‐induced YAP signaling. Issue 12 (22nd October 2020) - Wei, Leixin; Cao, Peng; Xu, Chen; Zhong, Huajian; Wang, Xiukun; Bai, Meizhu; Hu, Bo; Wang, Ruizhe; Liu, Ning; Tian, Ye; Chen, Huajiang; Li, Jinsong; et al.
Abstract: Loss of chondroitin sulfate (CS) has been reported to play a key role during intervertebral disc degeneration (IDD). However, the detailed mechanism of CS and its synthases have not been elucidated. Since CS is mainly synthesized by chondroitin synthases 3 (Chsy3), here, the Chsy3 knockout mice are generated by using CRISPR‐Cas9 and semi‐cloning technology to study its mechanism during IDD. We find that CS and Chsy3 expression are decreased during IDD both in human and mice nucleus pulposus (NP) tissue, and knockout of Chsy3 shows that spontaneous IDD phenotype resembles that of human samples in the Chsy3 −/− mice. Taking advantage of RNA‐Seq data, we confirm increased catabolic and decreased anabolic changes in Chsy3 −/− NP cells. By using bioinformatic analysis and validation, we find that Hippo signaling pathway is significantly downregulated, and the activation of Yap1 is mainly affected in Chsy3 −/− NP cells. Furthermore, functional analyses have shown that Chsy3 could regulate NP cell degeneration by Actin tension mediated activation of Yap1, which is independent of Hippo/Lats signaling. In summary, our findings reveal a novel mechanism that depletion of CS‐related Chsy3 can cause spontaneous intervertebral disc degeneration by mediating Yap activation through CS‐related actin‐tension in NP cells.